Electrical stimulation minimizes muscle metabolic alterations during and after immobilization of rats hindlimb (Fisioterapia e Pesquisa, 2006)
This study aimed at assessing the effect of electrical stimulation (ES) in muscles metabolic profile and weight of rats hindlimb during the limb immobilization period and after casts were removed. Thirty-six Wistar rats were divided into 6 groups: control (C); control but receiving ES (CES); immobilized (Im); immobilized receiving ES during immobilization (ImEE); immobilized and observed during recuperation for seven days after cast removal (ImR); and immobilized and receiving ES during recuperation for seven days after cast removal (ImREE). After the experimental period the soleus (S), white gastrocnemius (WG), red gastrocnemius (RG), anterior tibial (AT) and extensor digitorum longus (EDL) muscles were collected for analysis of glycogen reserves (GR), besides S and EDL weight evaluation. Results show that, in the Im group, immobilization caused significant GR and muscle weight reduction. Inversely, ES produced significant GR increase in CEE and ImEE groups, but did not interfere in muscle weight. During recuperation after cast removal, the group that did not receive ES (ImR) showed significant reductions in muscle GR and weight, while in the ImREE group there was significant increase in RG (257.9% S, 308.1% WG, 343.3% RG, 312% AT, 240.7% EDL) and in EDL weight (12%). ES thus minimized deleterious effects both during and after immobilization, pointing to its great efficiency in clinical treatment situations of muscle disuse.